An asphalt pavement testing apparatus and a method. - Muniandy, Ratnasamy (2007)

(untitled)
A road testing apparatus for testing an asphalt pavement extending from a first end to a second end comprises of a general rigid framework (10) on which a flat base (12) is placed thereon, a slideable support member (16) slideably moveable along the flat base (12), a jacking means (20) mountable at the bottom portion of the flat base (12), a rain simulator (22) disposed above the flat base (12) and a compactor member (24) and an axle load member mountable to the slideable support member (16).